DESIGNING MITIGATION ACTION STRATEGIES BASED ON RISK ANALYSIS OF IN-HOUSE MANUFACTURING SUPPLY CHAIN AT PT. SAFTA FERTI - Herdiani, Leni; Cui, Zhenyu; Ramadina, Amalia; Nursaimatussaddiya, Nursaimatussaddiya; Sihombing, Eka (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
The obstacles that occur as a result of supply chain risks in in-house manufacturing supply chain activities at PT Safta Ferti, make PT Safta Ferti unable to achieve optimal customer satisfaction, for PT Safta Ferti which is engaged in manufacturing services with production and repair activities of Mechanical Parts, especially Rotating Parts and other in-machine drive component products, customer satisfaction is the main goal which is one of the keys to business success. To minimize this, an analysis of the risks in the in-house manufacturing supply chain activities at PT Safta Ferti using the house of risk (HOR) method which consists of two phases, namely house of risk phase 1 (HOR1) and house of risk phase 2 (HOR2) with supply chain activity mapping using the supply chain operation reference (SCOR) model, based on the results of data processing with the HOR method, it is known that there are 63 risk events and 90 identified risk agents along the flow of in-house manufacturing supply chain activities at PT Safta Ferti with 22 risk agents. Safta Ferti with 22 priority risk agents selected in HOR1 on the basis of the use of the Pareto diagram principle with a ratio of 63:24 to take proactive action in HOR2 so that 28 draft mitigation action strategies (preventive action) are obtained along with the priority of their implementation related to 22 priority risk agents.